‘MY ANCESTORS WERE DISPLEASED WITH ME’ – CHILDHOOD EMBODIMENT OF VARIANT INTERSEX DEVELOPMENTS IN SOUTH AFRICA - Brown, Anthony (International Journal of Humanity Studies (IJHS), 2025)
South Africa constitutionally promotes affirmative gender and sexual diversity education, but the curriculum assumes normative bodies with binary classifications of external genitalia. Children born with intersex development present variant chromosomal, gonadal, or genitalia that deviate from the norm. Lensed through the Theory of Unintelligibility, these bodies are seen as ambiguous and derogatively labelled as hermaphrodites or Disorders of Sex Development (DSD), making them incapable of integration into socio-educational environments. This phenomenological study explores how young adults born with variant intersex characteristics learned about and embodied their sexual identity during their school years, using in-depth interviews with six participants selected with the support of Intersex South Africa. The evidence shows that participants lived in confusion for a large part of their childhood due to frequent hospital visits, examinations, surgeries, and family reactions without explanation. Learning about male and female bodies at school confirmed the messages about their abnormal bodies, resulting in self-hate and isolation. There is a need for child psychology services to support medical professionals, families, and educators in addressing variant intersex developments, providing trauma therapy for children, and including intersex development alongside normative sex development in sexuality education and awareness.